THE EFFECT OF DEMOCRATIC LEADERSHIP STYLE ON THE PERFORMANCE OF KKM MEMBERS OF MTS CITY OF SUKABUMI - Nana Suryana; Mulyawan Safwandy Nugraha (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to determine the influence of democratic leadership style on performance at KKM MTs Sukaumi City. The variables used in this study were Democratic Leadership Style as the dependent variable and the performance variable of the MTs KKM Members as the independent variable, while data collection techniques used observation and field studies in this study, the researcher interacted directly with all members of the MTs KKM Sukabumi City. The results of this study indicate that there is a significant influence between democratic leadership style on the performance of KKM MTs Sukabumi members. Researchers get information and facts, that the attitude of the KKM MTs Sukabumi City leaders is democratic, harmonious communication is established between the chairman and its members, the chairman always provides joint performance motivation for its members.